Patient’s autonomy from a biethical perspective. - Adriana Ribeiro-Alves (Journal of Oral Research, 2012)
Even though the conflicts arising in the field of Bioethics are generated by biomedical advances, these problems are meta-medical, that is they are transverse to all disciplines with scope in the human health. In this context, the application of bioethical principles such as the principle of autonomy, is considered a starting point, crucial to decision making referring to the exercise of medical and dental practice. In this sense, it is necessary to increase efforts through health policies and formation at the highest level for professionals in health disciplines in order to guide them to reduce violations of bioethical principles, as indeed happens in the day by day practice, in health services, both public and private, clinics or hospitals in order to get a health system with a more humanistic commitment. Thus, bioethics must be the base on which lay the foundations of a necessary dialogue that tends to resolve the observed conflicts, seeking to have the human being, and dignity of life as essential issues of their actions. The aim of this review is not to propose a definition of the Principle of Autonomy, that everyone already handle, but invite to a reflexion which contributes to size it and apply it in the field of dental practice in a bioethical context linked to the human person.